Optimization Modeling of Ethanol Production from Shorgum bicolor grain: Comparison between Separate Hydrolysis Fermentation and Simultaneous Saccharification Fermentation - RUTH CHRISNASARI; DAMIATI HARTINI SUSETYO; ADRIAN PRATAMA SUGIANTO; TJANDRA PANTJAJANI (Microbiology Indonesia, 2013)
Two different process configurations, simultaneous saccharification and fermentation (SSF), and separate hydrolysis and fermentation (SHF), were compared for ethanol production from Shorgum bicolor grain. Optimization modeling for glucoamylase and Zymomonas mobilis concentration in both of SSF and SHF were carried out to obtain optimal concentration of ethanol production. The optimum condition was achieved using 0.021 % (v/v) of glucoamylase, and 30.19% (v/v) of Z. mobilis for SHF. In contrast, the optimum condition for SSF was 0.021 % (v/v) of glucoamylase and 17.51% (v/v) of Z. mobilis. The model predicted SHF processing to be superior. The superiority of SHF over SSF was confirmed experimentally, the result showed ethanol yield of SHF was 134.80 g L-1 and ethanol yield of SSF was 115.66 g L-1 after 72 h incubation time. A high similarity was observed between the predicted and experimental results, demonstrating the accuracy of the model.